Analisis Kinerja Dewan Pengawas Syariah (DPS) Terhadap Kegiatan Operasional Pada KSSPS BMT Sri Sejahtera Jawa Timur. - Putri Pratama, Agustina Sintya (Jurnal Ekonomika dan Bisnis Islam, 2020)
Shariah Supervisory Board (DPS) is the most important part in Islamic financial institutions and is the guarator of the implementation of shariah principles in accordance with Minister of Cooperatives and Small Medium Entreprises Regulation No.11/PER/M.KUKM/XII/2017 concerning the Implementation of Sharia Loan Savings and Loan Business Activities which requires the Sharia Supervisory Board (DPS). In addition there are requirements specified in Minister of Cooperatives Regulation No.16/PER/M.KUKM/IX/2015 concerning the Implementatuon of Savings and Loan Business Activities Financing bu Cooperatives that must be met so that there are no irregularities in any sharia cooperatives activities. This study uses descriptive qualitative methods that aim to determine the performance of the Sharia Supervisory Board (DPS) in operational activities at KSPPS BMT Sri Sejahtera Jawa Timur. From the results if the research conducted that supervision activities carried out by the Sharia Supervisory Board (DPS) with direct supervision through reports from managers can be said to be less that optimal because supervision activities carried out are flexible and not only carried out on one Islamic financial institutions. In addition, public insight about the importance of the Sharia Supervisory Board (DPS) is less than optimal.